Estimating of the amount of sediments that reach to Balluran’s dam lake - وكيل محمد سعيد; عز الدين حسن; إبراهيم يزبك (Latakia University Journal -Engineering Sciences Series, 2023)
This research aims to create a map of the quantities of soil lost in Balluran Dam watershed, estimate the average total amount of potential erosion, and calculate the ratio between the amount of sediment arriving at the lake to total sediment estimated, and propose appropriate solutions to reduce the quantities of these sediments and mitigate their negative impact. This study included calculating the sediments amount resulting from soil water erosion using the revised universal soil loss equation (RUSLE) and (GIS) techniques, where a map was prepared representing the quantities of eroded soil in the research area in each partial cell of ​​(29.7x29.7) m2, and then the erosion rates in the region were classified into five classes according to international references. The study concluded that the annual amount of measured sediments reaching the lake is (15758 ton), and this quantity constitutes 40% of the total annual amount of calculated sediments resulting from soil water erosion, which is equivalent to (40044 ton) and constitutes the actual value of sediments that reach the Belloran Dam lake through the river water, which negatively affects the storage capacity of the dam lake, and this calls for finding appropriate solutions to reduce transferred sediments amount.